Modelo de alojamiento temporal para la atención de damnificados de desastres en el Departamento del Huila (2024)
The Temporary Housing model for emergency care is a project that is proposed as a result of the identification of the problems that arise when an emergency occurs due to a disaster, where the housing infrastructure is affected, causing large habitability deficits. scales, this deficit not only compromises people's health and well-being, but also hinders their ability to recover and thrive. The lack of adequate and safe accommodation exposes people to unhealthy and dangerous living conditions, aggravating their vulnerability. The objective of the project is to develop a temporary accommodation model that meets international standards of habitability and decent housing, specifically those established in the Humanitarian Charter and Minimum Standards for Humanitarian Response. The model must meet the basic needs of affected communities, providing a safe, decent and adequate shelter to live in while working on permanent housing solutions.